House prices, consumption and the role of non-mortgage debt - Katya Kartashova; Ben Tomlin (Bank of Canada, 2013)
This paper examines the relationship between house prices and consumption, through the use of debt. Using unique Canadian household-level data that reports the uses of debt, we begin by looking at the relationship between house prices and debt. Using quantile regression, we find a positive and significant relationship between regional house prices and total household debt all along the conditional debt distribution. This suggests that the household-level relationship between house prices and debt goes beyond the purchase of real estate. We then find a positive relationship between house prices and non-mortgage debt (the sum of secured lines of credit, unsecured lines of credit, leases and other consumer loans, except for credit cards) for homeowners. Combining these results with the reported uses of non-mortgage debt allows us to connect house prices and nonhousing consumption - this connection is new to the literature on house prices and consumption. We conclude that the increases in house prices over the 1999-2007 period were, indeed, associated with an increase in non-mortgage debt and non-housing consumption. Our results can be thought of as the establishment of a conservative lower bound for the overall relationship between house prices and aggregate consumption.
Keywords: E21; D10; D14; D31; 330; Credit and credit aggregates; Domestic demand and components